Effect of chirality of L/D-proline and prochiral glycine as the linker amino acid in five-atom linked thymidinyl-(alpha-aminoacid)-thymidine dimers - Seema Bagmare; D'Costa, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2009)
The chirality of the amide linker in dimer blocks was found to have a profound effect on the orientation of base stacking interactions as studied by CD and NMR spectroscopy.